DIFFERENTIATION OF THE RATE OF THE TAX ON INCOMS OF THE PHYSICAL PERSONS - N.P. REMIZOV (Advanced Engineering Research, 2007)
In this article is considered model of the calculation of the optimized rates of the taxes on incomes of the natural persons. These rates are defined for each group of taxpayers and depend on level of their incomes. The use of this model provides the improvement of the social-economic situation of society, refusal of the «envelop» schemes of payments of the salaries, full budget execution. The article carries the theoretical nature. Model, which is described in the article, has a high level of potential efficiency from the practical application, which, in it's turn, requires legislative statement.